Diethyldithiocarbamate-ferrous oxide nanoparticles inhibit human and mouse glioblastoma stemness: aldehyde dehydrogenase 1A1 suppression and ferroptosis induction - Abu-Serie, Marwa M.; Osuka, Satoru; Heikal, Lamiaa A.; Teleb, Mohamed; Barakat, Assem; Dudeja, Vikas (Frontiers in Pharmacology, 2024)
The development of effective therapy for eradicating glioblastoma stem cells remains a major challenge due to their aggressive growth, chemoresistance and radioresistance which are mainly conferred by aldehyde dehydrogenase (ALDH)1A1. The latter is the main stemness mediator via enhancing signaling pathways of Wnt/β-catenin, phosphatidylinositol 3-kinase/AKT, and hypoxia. Furthermore, ALDH1A1 mediates therapeutic resistance by inactivating drugs, stimulating the expression of drug efflux transporters, and detoxifying reactive radical species, thereby apoptosis arresting. Recent reports disclosed the potent and broad-spectrum anticancer activities of the unique nanocomplexes of diethyldithiocarbamate (DE, ALDH1A1 inhibitor) with ferrous oxide nanoparticles (FeO NPs) mainly conferred by inducing lipid peroxidation-dependent non-apoptotic pathways (iron accumulation-triggered ferroptosis), was reported. Accordingly, the anti-stemness activity of nanocomplexes (DE-FeO NPs) was investigated against human and mouse glioma stem cells (GSCs) and radioresistant GSCs (GSCs-RR). DE-FeO NPs exhibited the strongest growth inhibition effect on the treated human GSCs (MGG18 and JX39P), mouse GSCs (GS and PDGF-GSC) and their radioresistant cells (IC50 ≤ 70 and 161 μg/mL, respectively). DE-FeO NPs also revealed a higher inhibitory impact than standard chemotherapy (temozolomide, TMZ) on self-renewal, cancer repopulation, chemoresistance, and radioresistance potentials. Besides, DE-FeO NPs surpassed TMZ regarding the effect on relative expression of all studied stemness genes, as well as relative p-AKT/AKT ratio in the treated MGG18, GS and their radioresistant (MGG18-RR and GS-RR). This potent anti-stemness influence is primarily attributed to ALDH1A1 inhibition and ferroptosis induction, as confirmed by significant elevation of cellular reactive oxygen species and lipid peroxidation with significant depletion of glutathione and glutathione peroxidase 4. DE-FeO NPs recorded the optimal LogP value for crossing the blood brain barrier. This in vitro novel study declared the potency of DE-FeO NPs for collapsing GSCs and GSCs-RR with improving their sensitivity to chemotherapy and radiotherapy, indicating that DE-FeO NPs may be a promising remedy for GBM. Glioma animal models will be needed for in-depth studies on its safe effectiveness.